THE BASIC PRINCIPLES OF THE INTEGRATED MANAGEMENT OF THE PROCESS OF ASSEMBLY AND THREADING - Anton Skorkin; Oleg Kondratyuk (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of this article is the issues related to the integrated management of assembling operations of fastening and threading elements at all stages of their implementation. The goal is to develop the generalized structure of the data management system of the process of assembly and threading. The objectives are: to justify the principles of managing the assembly and threading process at each stage of the assembly to improve the efficiency of these operations, to study the power, accuracy and performance characteristics of the connections and to draw the conclusion that suggested the theory of assembly management is efficient. The following results are obtained. The article presents the analytical dependencies of the force indexes of threading in the course of the package and sheet assembly, including the tightening force while joining; the assembly of a multilayered package of dissimilar sheet materials was analyzed. On the basis of the theoretical analysis, the dependences of the power indices of threading during the package and sheet assembly were determined. The assembly of the package of sheet materials was investigated, including a multilayered package of dissimilar materials of a “metal-plastic” type. Conclusions. The process of assembling threaded joints with the use of management principles was used; these principles enable increasing the efficiency of the assembly process, reducing the complexity of the basic operations, and improving the quality of the joints obtained. The use adaptive control of the screwing speed on the main threading transitions is suggested for reducing the torque.  The technology of making threaded joints with given properties is developed, the main ways of increasing the efficiency of assembly and threading processes are determined on the basis of the integrated control system for the assembly process.